Comparing the effect of aerobic continuous and interval training and detraining on cardiac hypertrophy and atrophy - عباسعلی گائینی; فهیمه کاظمی; جواد مهدی آبادی (فیزیولوژی ورزش و فعالیت بدنی)
Purpose: The purpose of this study was to compare the effect of aerobic continuous and interval training anddetraining on myocardial adaptations. Methods: Twenty male none- athlete students were volunteered anddivided randomly into aerobic continuous (n= 10) and aerobic interval group (n=10). Subjects participated inan 8-week running program (3 day/week, at 70% HRmax). Continuous group ran continuously 45 min andinterval group ran five nine- min periods with a four– min inactive rest between the work periods. After 8-weekof training, subjects completed 4-week detraining. Paired sample t-test was used for analyzing data. Results:Using echocardiography, no significant difference was found in EDD, ESD, %FS, %EF, PWT, LA, AO, HR,SBP and DBP after 8-week continuous and interval training compared to before training (P>0.05), but asignificant difference was found in IVS (p<0.05). No significant difference was found in EDD, ESD, %FS,%EF, PWT, LA, AO, HR, SBP and DBP after 4-week detraining compared to 8-week continuous and intervaltraining (P>0.05), but a significant difference was found in IVS (p<0.05). Conclusion: Aerobic continuous andinterval training and detraining can affect on myocardial adaptations equally.